2018
DOI: 10.5943/mycosphere/9/1/1
|View full text |Cite
|
Sign up to set email alerts
|

Mycosphere Notes 102–168: Saprotrophic fungi on Vitis in China, Italy, Russia and Thailand

Abstract: This is the third paper in the series, Mycosphere notes, wherein we provide notes on various fungal taxa. In this set of notes, we deal with species found on the grape genus, Vitis, one of the most important economically important crops, grown worldwide. We provide notes on 67 taxa, including two new species, Alternaria italica and Alfaria vitis, an asexual morph for Alfaria cyperiesculenti and 41 new host records or distribution records. The taxonomic placement of most taxa discussed in this study is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Thus, during the past decade, a polyphasic approach, employing multi-locus DNA data together with morphology and ecology, has been employed for species boundaries in the genus (Crous et al 2012, Udayanga et al 2014a, b, Huang et al 2015, Gao et al 2016, 2017, Guarnaccia and Crous 2017, 2018, Hyde et al 2017, 2018, Yang et al 2017a, b, 2018, Guarnaccia et al 2018, Jayawardena et al 2018, Perera et al 2018a, b, Tibpromma et al 2018, Wanasinghe et al 2018). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, during the past decade, a polyphasic approach, employing multi-locus DNA data together with morphology and ecology, has been employed for species boundaries in the genus (Crous et al 2012, Udayanga et al 2014a, b, Huang et al 2015, Gao et al 2016, 2017, Guarnaccia and Crous 2017, 2018, Hyde et al 2017, 2018, Yang et al 2017a, b, 2018, Guarnaccia et al 2018, Jayawardena et al 2018, Perera et al 2018a, b, Tibpromma et al 2018, Wanasinghe et al 2018). …”
Section: Discussionmentioning
confidence: 99%
“…Although the classification of Diaporthe has been on-going, species are currently being identified based on a combination of morphological, cultural, phytopathological and phylogenetical analyses (Gomes et al 2013, Huang et al 2013, 2015, Udayanga et al 2014a, b, 2015, Fan et al 2015, Du et al 2016, Gao et al 2016, 2017, Guarnaccia and Crous 2017, Hyde et al 2017, 2018, Guarnaccia et al 2018, Jayawardena et al 2018, Perera et al 2018a, b, Tibpromma et al 2018, Wanasinghe et al 2018). However, fungi isolated from forest trees in China were recorded in old fungal literature without any living culture and molecular data (Teng 1963, Tai 1979, Wei 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent identification of isolated taxa have incorporated analyses of ITS sequence data (Guo et al 2003;Promputtha et al 2007), Peregrine and Siddiqi (1972), Gonzalez and Tello (2011) Fungal Diversity Makovetz (1933), Stevenson and Wellman (1944), Mujica and Vergara (1945), Nasyrov (1964), Sarbhoy et al (1971), Pantidou (1973, Giatgong (1980), Bechet and Sapta-Forda (1981), Zhang (2003), Zhuang (2005) Whiteside (1966), Cook and Dubé (1989), Setati et al (2015), Michailides et al (2002), Kobayashi (2007), Vitale et al (2008), Bobev (2009), Casieri et al (2009, Gonzalez and Tello (2011), Dissanayake et al (2018), This study, Jayawardena et al (2018) Fungal Diversity Milholland (1994), Phillips (1998Phillips ( , 2000, Slippers et al Raabe et al (1981), Lee et al (1991), Mendes et al (1998), Holevas et al (2000), Phillips (2000), Gadgil (2005) C. fasciculatum Corda Cladosporiaceae Russia, Spain, Uzbekistan Gonzalez Fragoso (1921), Nagorny (1930) C. herbarum (Pers.) Link Cladosporiaceae P, E Fruit rot Australia,Chile, Spain …”
Section: Microfungi Collected From China Italy Russia and Thailandmentioning
confidence: 99%
“…In their study using multigene analyses the species were identified. ITS sequence data alone can be used in identification to genus or the species complex levels (Jayawardena et al , 2018a, but it has insufficient information to provide a better resolution at species or below species level.…”
Section: Colletotrichum Cordamentioning
confidence: 99%
“…OTUs could be assigned to species complexes but phylogenetic placement was ambiguous hence the reliability of the ITS is being questioned. For a better resolution of this genus protein coding gene regions are required (Jayawardena et al 2018a) but how far are we going to favour the use of alternative genes should we be dealing with OTUs suspected to be plant pathogens for a stable classification and appropriate nomenclature.…”
Section: Colletotrichum Cordamentioning
confidence: 99%